Seroepidemiology of Human Parvovirus B19 in 5-25 Year Old Age People in Iran - V Salimi; MM Gouya; AR Esteghamati; A Safaie; R Heshmat; Z Saadatmand; T Mokhtari-Azad (Tehran University of Medical Sciences, 2008)
Background: Parvovirus B19 (B19) is the only member of the family Parvoviridae associated with human infection. Although there are some studies to estimate the immunity to parvovirus in various populations but there is no seroepidemiological survey from Iran until now thus the age-specific immunity to human parvovirus infection was estimated. Methods:  A subset sample of 1500 study subjects in 2004 after Measles and Rubella mass campaign was selected from the original samples of 5000 sera kept at the Department of Virology in Tehran University of Medical Sciences. All sera were tested by a commercial ELISA kit. Results: Totally, 1303 (86.6%) of 1500 study subjects were seropositive for B19 IgG antibody. The seropositive rate of males and females were 85.3% and 88%, respectively (P= 0.129). The overall B19 seropositive rates in rural and urban were 84.3% and 88%, respectively (P= 0.044).  The seropositive rates were found to increase significantly with age and ranged from 79.3% in 5-9 year old group to 93.5% in 20-25 yr old group (P= 0.000). Conclusion: Our results indicate that in spite of high prevalence of B19 antibody the importance of routine diagnosis of B19 infection in order to elucidate the etiology of some unexplained 'exanthemata diseases' especially in measles elimination and eradication phase is needed.